2015
DOI: 10.1371/journal.pone.0133594
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral and Bilateral Cortical Resection: Effects on Spike-Wave Discharges in a Genetic Absence Epilepsy Model

Abstract: Research QuestionRecent discoveries have challenged the traditional view that the thalamus is the primary source driving spike-and-wave discharges (SWDs). At odds, SWDs in genetic absence models have a cortical focal origin in the deep layers of the perioral region of the somatosensory cortex. The present study examines the effect of unilateral and bilateral surgical resection of the assumed focal cortical region on the occurrence of SWDs in anesthetized WAG/Rij rats, a well described and validated genetic abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 79 publications
1
14
0
Order By: Relevance
“…Therefore, it has been suggested that absence seizures in this strain may in fact, have a bi-lateral focal origin (Luttjohann et al, 2011;Meeren et al, 2002;van Luijtelaar and Sitnikova, 2006). In agreement with this, it has recently been demonstrated that the removal of only both foci completely abolishes SWDs (Scicchitano et al, 2015) while fMRI (functional magnetic resonance imaging) studies have confirmed the presence of bilateral activated regions in the somatosensory cortex . Based on this background, we can then suppose that these focal epileptic areas may be genetically predetermined to be hyperexcitable (D'Antuono et al, 2006;Kole et al, 2007;Luttjohann et al, 2011;Strauss et al, 2004) from a certain developmental age onwards.…”
supporting
confidence: 53%
“…Therefore, it has been suggested that absence seizures in this strain may in fact, have a bi-lateral focal origin (Luttjohann et al, 2011;Meeren et al, 2002;van Luijtelaar and Sitnikova, 2006). In agreement with this, it has recently been demonstrated that the removal of only both foci completely abolishes SWDs (Scicchitano et al, 2015) while fMRI (functional magnetic resonance imaging) studies have confirmed the presence of bilateral activated regions in the somatosensory cortex . Based on this background, we can then suppose that these focal epileptic areas may be genetically predetermined to be hyperexcitable (D'Antuono et al, 2006;Kole et al, 2007;Luttjohann et al, 2011;Strauss et al, 2004) from a certain developmental age onwards.…”
supporting
confidence: 53%
“…Absence seizures in rodents are most prominent in the somatosensory cortices (Meeren et al, 2002;Polack et al, 2007;Scicchitano et al, 2015). We reasoned that if abnormally increased myelination is caused by seizure activity, these changes would be specific to the seizure-affected regions.…”
Section: Myelination Increases Within Corpus Callosum Regions Affectementioning
confidence: 99%
“…Accordingly, seizures in WAG/Rij rats could have a bilateral focal origin [24][25][26]. Very recently, it has been described as the surgical removal of both foci, in these rats, totally abolished SWDs [24]. According to these evidence, it is possible to hypothesize that these focal epileptic areas could be genetically programmed to become hyperexcitable [25,27,28].…”
Section: The Genetically-programmed Epileptogenic Process In Wag/rij mentioning
confidence: 98%
“…Several studies, performed in WAG/Rij in rats, have affirmed that, in this strain, exists a focally increased excitability in the deep layers of the perioral region of somatosensory cortex, where the SWDs arise. Accordingly, seizures in WAG/Rij rats could have a bilateral focal origin [24][25][26]. Very recently, it has been described as the surgical removal of both foci, in these rats, totally abolished SWDs [24].…”
Section: The Genetically-programmed Epileptogenic Process In Wag/rij mentioning
confidence: 99%